Analisis Faktor Ketidakpatuhan Pelaporan Dana Kampanye Parpol Peserta Pemilu Kota X Pada Pemilu Tahun 2024 - Dipta Wira Hanggara; Hero Priono (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The campaign in the context of the General Election is an important activity for Political Party X in City P, aimed at winning mass support. However, issues have arisen regarding the transparency and accountability of campaign fund reporting, particularly due to the lack of expenditure transaction evidence for some activities recorded in the financial reports. This creates ambiguity and increases the potential for fraud in the management of campaign finances. To address this, a strategy is needed that includes enhancing transparency in campaign fund reporting, training for campaign fund managers, and conducting regular audits by independent and trusted parties. It is hoped that this will improve compliance with campaign fund regulations and build public trust. The research methodology used is a qualitative descriptive approach, with analysis focused on document evaluation and interviews to identify non-compliance in campaign fund reporting by Political Party X.